2017
DOI: 10.3390/toxins9070197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mycotoxins Secreted by Aspergillus Molds on the Inflammatory Response of Human Corneal Epithelial Cells

Abstract: Exposure to molds and mycotoxins not only contributes to the onset of respiratory disease, it also affects the ocular surface. Very few published studies concern the evaluation of the effect of mycotoxin exposure on ocular cells. The present study investigates the effects of aflatoxin B1 (AFB1) and gliotoxin, two mycotoxins secreted by Aspergillus molds, on the biological activity of the human corneal epithelial (HCE) cells. After 24, 48, and 72 h of exposure, cellular viability and inflammatory response were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Mercury [31] and environmental toxins [56] are now being linked to immune dysfunction and have been linked to the worldwide increase in autoimmune disease [27], and ADHD [57]. Mold toxins [28] have been associated with chronic fatigue syndrome, upper respiratory illness, and specifically gliotoxins, found in elevated levels in this patient, have been shown to be immunosuppressive [58]. The patient's elevated C4a level and TGFB-1 levels are biomarkers seen with Chronic Inflammatory Response Syndrome (CIRS) associated with mold exposure and brain injury [59].…”
Section: Discussionmentioning
confidence: 96%
“…Mercury [31] and environmental toxins [56] are now being linked to immune dysfunction and have been linked to the worldwide increase in autoimmune disease [27], and ADHD [57]. Mold toxins [28] have been associated with chronic fatigue syndrome, upper respiratory illness, and specifically gliotoxins, found in elevated levels in this patient, have been shown to be immunosuppressive [58]. The patient's elevated C4a level and TGFB-1 levels are biomarkers seen with Chronic Inflammatory Response Syndrome (CIRS) associated with mold exposure and brain injury [59].…”
Section: Discussionmentioning
confidence: 96%
“…Coinfections, like Mycoplasma [34] and Bartonella [239,240], as well as environmental toxins have also been associated with immunological dysfunction. Mycoplasmas can interact with B cells [33], affecting antibody production, and mercury [50], along with other environmental toxins [51] (including gliotoxins, which have been shown to be immunosuppressive), have been linked to immune dysfunction and a worldwide increase in autoimmune disease [37,241].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the human studies [ 36 , 37 , 39 , 40 ], organic bioaerosols have also been reported to negatively impact ocular surface health. In an in-vitro study, human corneal epithelial (HCE) cells were exposed to various concentrations of mycotoxins (AFB 1 and gliotoxin) vs. a solvent control, and in vitro assays were done to asses cellular viability and inflammatory responses [ 45 ]. Exposure to AFB 1 (16 µg/mL) increased expression of several inflammatory markers (380-fold increase in IL-8, 160-fold increase in C-X-C motif chemokine ligand 1, 21-fold increase in TNF-α) compared to the control.…”
Section: Effect Of Particulate Matter (Pm) On the Ocular Surfacementioning
confidence: 99%